Pembelajaran Akhlak Berbasis Teori Keseimbangan Perilaku Moral - Nunung Nursyamsiah (Jurnal Studi Agama dan Masyarakat, 2017)
This study examines the characteristics of teaching materials that can lead to moral feeling conflict; a classroom activity model that can reinforce moral feeling conflict, followed by a change of moral feeling until the occurrence of an imbalance of moral feeling; and the characteristics of lecture assignments that can encourage the process of internalization of character values and enable the occurrence of the values actualization in student life. The subjects of the study are Arabic Language Education students who take Tahdzibul Akhlaq course in the even semester of 2013/2014. Based on the results of interviews, observations, and documentation of students’ muhasabah report, it can be concluded that teaching material with contextual material which is related to the students’ life experience has great potential to create moral feeling conflict. The process of reflection in class discussions about the material can create an imbalance of students' moral feelings that triggered the internalization process. Meanwhile, lecture assignments that are able to create internalization of character values productively are field tasks, they are observation of real life from the surrounding environment according to the teaching material and also observation that is related to the life experience of the students so that there is a change of moral feeling.